2020
DOI: 10.21203/rs.3.rs-83176/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular electrocatalysts transform CO into C2+ products effectively in a flow cell

Abstract: The highest performance flow cells capable of electrolytically converting CO2 into higher value chemicals and fuels pass a concentrated hydroxide electrolyte across the cathode. A major problem for CO2 electrolysis is that this strongly alkaline medium converts the majority of CO2 into unreactive HCO3– and CO32– rather than CO2 reduction reaction (CO2RR) products. The electrolysis of CO (instead of CO2) does not suffer from this same problem because CO does not react with hydroxide. Moreover, CO can be more re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…So far, only copper-based catalysts with varying morphologies have been demonstrated to reduce CO 2 or CO with a reasonable selectivity and reaction rates to C 2+ products. In Table S1, we have compiled a list of landmark studies that reported current densities higher than 100 mA/cm 2 for CO2R to C 2+ products. In Table S2, a compilation of interesting studies on CO reduction to C 2+ products is provided. We note that several studies reported high FEs for C 2+ products but at much lower CDs, which is less interesting from an economic point of view and have been excluded from the list. As noted by Romero Cuellar et al and Xia et al, COR has a few advantages compared to CO2R: (1) the FEs for C 2+ products are higher, because COR typically requires a lower number of electrons for a specific product; (2) the current densities are higher due to the higher reactivity of CO, which results in a higher single-pass conversion of CO; (3) the cell potential is lower for COR and (4) the CO 2 utilization efficiency is higher for COR because of the parasitic loss of CO 2 in CO2R due to reactions with the electrolyte.…”
Section: State Of the Art Of Co2r And Cor To C2+ Productssupporting
confidence: 94%
“…So far, only copper-based catalysts with varying morphologies have been demonstrated to reduce CO 2 or CO with a reasonable selectivity and reaction rates to C 2+ products. In Table S1, we have compiled a list of landmark studies that reported current densities higher than 100 mA/cm 2 for CO2R to C 2+ products. In Table S2, a compilation of interesting studies on CO reduction to C 2+ products is provided. We note that several studies reported high FEs for C 2+ products but at much lower CDs, which is less interesting from an economic point of view and have been excluded from the list. As noted by Romero Cuellar et al and Xia et al, COR has a few advantages compared to CO2R: (1) the FEs for C 2+ products are higher, because COR typically requires a lower number of electrons for a specific product; (2) the current densities are higher due to the higher reactivity of CO, which results in a higher single-pass conversion of CO; (3) the cell potential is lower for COR and (4) the CO 2 utilization efficiency is higher for COR because of the parasitic loss of CO 2 in CO2R due to reactions with the electrolyte.…”
Section: State Of the Art Of Co2r And Cor To C2+ Productssupporting
confidence: 94%